Influence of permeation modes on oxygen permeability of the multichannel mixed-conducting hollow fibre membrane. (27th January 2015) - Zhu, Jiawei; Liu, Zhengkun; Guo, Shaobin; Jin, Wanqin
Abstract: A multichannel mixed-conducting hollow fibre (MMCHF) membrane, Ba0.5 Sr0.5 Co0.8 Fe0.2 O3− δ, has been successfully prepared by a combined phase inversion and sintering technique. Two possible permeation modes can be used in the hollow fibre membrane. One mode is that oxygen permeates from the shell side of the membrane to the lumen side (SL mode), with the other mode being in the direction from the lumen side to the shell side (LS mode). Thus, it is necessary to study oxygen permeability in these two modes to make better use of the membrane. In this work, the influences of oxygen permeation modes on separation performance of MMCHF membrane were investigated systematically. In LS mode, the MMCHF membrane obtains a high oxygen flux of 3.22 ml min −1 cm −2 which is higher than that in SL mode. The surface reaction is the rate-limiting step for oxygen transport in the two modes and the surface reaction resistance of LS mode is smaller than that of SL mode. Our work demonstrates that when the MMCHF membrane adopts LS mode, it is beneficial to obtain higher oxygen flux. Highlights: A multichannel mixed-conducting hollow fibre membrane was prepared. The membrane has high oxygen permeation flux and excellent mechanical strength. Surface oxygen exchange reaction is the rate-limiting step for oxygen permeation. When oxygen permeates from lumen side to shell side, it can obtain higher oxygen flux.